INTERPRETATION OF PSYCHOLOGICAL STATES IN "MISS BRILL" BY KATHERINE MANSFIELD. (Multidisciplinary Journal of Science and Technology, 2025)
This article provides a detailed psychological analysis of the protagonist, Miss Brill, from Katherine Mansfield’s short story "Miss Brill." The paper focuses on the psychological states of loneliness, social disconnection, self-deception, and eventual emotional collapse, illustrating how these themes are central to Miss Brill’s character development. The analysis uses literary techniques such as symbolism, imagery, irony, and psychological concepts to explore how Miss Brill constructs and eventually faces the harsh reality of her isolation. Through her weekly park visits, Miss Brill creates a fantasy of connection, perceiving herself as an important participant in the lives of those around her. However, the story’s climax—when Miss Brill overhears a young couple mock her—forces her to confront the painful truth of her invisibility and social irrelevance. The article applies psychological frameworks, including Carl Rogers’ self-concept and Freud’s defense mechanisms, to explain Miss Brill’s emotional coping strategies and her eventual withdrawal from reality. The fur stole, a key symbol in the story, mirrors Miss Brill’s emotional state and represents her vulnerability and deepening isolation. In conclusion, the article highlights how Mansfield’s portrayal of Miss Brill addresses broader themes of aging, identity, and the human need for connection in an indifferent world.